2023
DOI: 10.1007/s11701-023-01558-2
|View full text |Cite
|
Sign up to set email alerts
|

Robotic male and laparoscopic female sphincter-preserving total mesorectal excision of mid-low rectal cancer share similar specimen quality, complication rates and long-term oncological outcomes

Abstract: Background: The aim of this study was to compare perioperative and long-term oncological outcomes between laparoscopic sphincter-preserving total mesorectal excision in female patients (F-Lap-TME) and robotic sphincter-preserving total mesorectal excision in male patients (M-Rob-TME) with mid-low rectal cancer (RC).Methods: A retrospective analysis of a prospectively maintained database was performed. 170 cases (F-Lap-TME: 60 patients; M-Rob-TME: 110 patients) were performed by a single surgeon (January 2011 -… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…These studies once again demonstrated that robotic approach can potentially overcome some technical challenges related to pelvic anatomical differences between sexes compared to laparoscopy. However, our two previously published studies indicated that robotic approach did not provide any bene t in female patients with rectal cancer when compared with laparoscopy [29][30].…”
Section: Discussionmentioning
confidence: 78%
“…These studies once again demonstrated that robotic approach can potentially overcome some technical challenges related to pelvic anatomical differences between sexes compared to laparoscopy. However, our two previously published studies indicated that robotic approach did not provide any bene t in female patients with rectal cancer when compared with laparoscopy [29][30].…”
Section: Discussionmentioning
confidence: 78%
“…Recently, it has been proposed that the robotic approach may provide a better mesorectal specimen and local control compared to the laparoscopic technique in male patients with mid-low rectal cancer while the same research group has failed to show these benefits in female patients. [10,11] This suggests the robotic surgery may be superior, especially in the narrow pelvis. However, robotic surgery is expensive and difficult to access; selection criteria for rectal carcinoma cases may increase the benefits and cost-effectiveness of this technique.…”
Section: Discussionmentioning
confidence: 99%